Studies on the Growth and Reproduction of L mauritii during Vermicomposting of Jackfruit Leaf Litter with Bedding Material Mixture in Various Combinations - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Studies on the Growth and Reproduction of L mauritii during Vermicomposting of Jackfruit Leaf Litter with Bedding Material Mixture in Various Combinations